2021
DOI: 10.1371/journal.pone.0251155
|View full text |Cite
|
Sign up to set email alerts
|

Sexual health knowledge and needs among young adults with congenital heart disease

Abstract: Advances in the treatment of congenital heart disease (CHD) have increased life expectancy, entailing medical surveillance for a considerable number of adolescents and young adults with CHD for issues arising in areas such as sexual health. This study aimed to assess the sexual knowledge and the needs for sexual health education among this group. The participants comprised 53 young adult outpatients (27 males, median age: 23 years) who had undergone surgical interventions (median: 3 times) for CHD. The Knowled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…In Korea, ACHD patients scored lower on the Knowledge in Safe Sex Practice scale, especially those with complex cyanotic conditions. 13 Burstrom et al. identified that only 70% of adolescents with CHD could correctly identify whether sexual activity (SA) could worsen their heart condition.…”
Section: Sexual Behavior In People Living With Achdmentioning
confidence: 99%
“…In Korea, ACHD patients scored lower on the Knowledge in Safe Sex Practice scale, especially those with complex cyanotic conditions. 13 Burstrom et al. identified that only 70% of adolescents with CHD could correctly identify whether sexual activity (SA) could worsen their heart condition.…”
Section: Sexual Behavior In People Living With Achdmentioning
confidence: 99%
“…In this context, disease-related knowledge refers to understanding medical aspects related to CHD, including its complications, medical interventions, and disease management strategies. 42,43 Youth with CHD often have limited knowledge about topics such as physical activity, diet, and sexual health related to disease management, [44][45][46] and they frequently struggle to accurately locate their specific cardiac abnormalities and comprehend the complexities of cardiac defects and complications. 44,46 During the transition program, it is recommended to employ strategies such as creating portable electronic files like the MyHealth passport to provide information about heart conditions, and using diagrams to educate patients about anatomical defects.…”
Section: Effects Of Transition Interventionsmentioning
confidence: 99%
“…It may be important to initiate the education before adolescence. 35 Similarly, knowledge of contraception may be inadequate in patients with CHD. Each contraceptive method, including oral contraceptives, condoms, and intrauterine devices, has its own risks and benefits.…”
Section: Preconception Counseling and Contraception As Transitional Carementioning
confidence: 99%